Phatic interpretations: standarisation and conventionalisation - Nicolle, Steve; Clark, Billy (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 1998)
This paper builds on work by Zegarac and Clark (Zegarac and Clark, forthcoming; Zegarac, in press) on phatic communication. Zegarac and Clark define phatic interpretations as interpretations which depend on the recognition of a communicative intention (as defined by Sperber and Wilson 1986 and exploited in their definition of ostensive communication). This definition does not link phatic interpretations directly to social functions but does reflect the fact that phatic interpretations have social effects. The social effects follow from the fact that any act of ostensive communication is, by definition, social. Zegarac discusses how phatic interpretations become standardised and conventionalised. Here we explore the processes of standardisation and conventionalisation in more detail. A first glance at the phenomena suggests an interesting paradox. When a particular linguistic form becomes so frequently linked with phatic interpretations that this usage becomes conventionalised, Zegarac and Clark's definition seems to predict that utterances containing that form will no longer give rise to phatic interpretations (because the interpretation will depend on the linguistically-encoded meaning rather than on the recognition of a communicative intention). We consider an alternative approach to that proposed by Zegarac, which exploits the relevance-theoretic notion of procedural encoding. We show how such an approach might lead to the modification of a prediction of Zegarac and Clark, i.e. the claim that purely phatic interpretations arise only when non-phatic interpretations are not consistent with the principle of relevance.